185k views
3 votes
If (a-2)^2+(b+1)^2+(c-3)2 =0 then the value of a^2/4+b^2+c^2/3

User Yakhyo
by
5.8k points

2 Answers

3 votes

The correct answer is 2. a = 1/2, b = - 3, c = -2

Explanation:

1. Let's review the information provided for an answering the question correctly:

0 =1/2x^2- 3x- 2

0 = 1/2x² - 3x - 2

2. Let's find the values for a, b and c.

According to the quadratic equation, we have:

a = 1/2

b = - 3

c = - 2

The correct answer is 2. a = 1/2, b = - 3, c = -2

(❤´艸`❤)

User Michael Sohnen
by
6.0k points
4 votes

Answer:

5

Explanation:

(a-2)^2+(b+1)^2+(c-3)^2 =0

Since all 3 terms are square numbers, they must be = 0 to have a sum of 0.

so a-2= 0, b+1=0 and c-3= 0

  • a=2, b= -1, c= 3

a^2/4+b^2+c^2/3= 4/4+1+9/3= 1+1+3= 5

User Sugan S
by
5.8k points